Midsummer mysteries : secrets and suspense from the queen of crime - Christie, Agatha, 1890-1976 (HarperCollinsPublishers, 2021)
Soubor detektivních příběhů anglické královny žánru spojuje tématika léta.
Keywords: anglické povídky; detektivní povídky; výbory; English short stories; detective short stories; selected works